DINAMIKA PENYEDIAAN PUPUK SUBSIDI PADA USAHA TANI PADI SAWAH MELALUI MEKANISME RENCANA DEFINITIF KEBUTUHAN KELOMPOK TANI (RDKK) DI KOTA KENDARI - Nurliana Nurliana; Yani Taufik; L. Daud (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
The purpose of this study was to determine the dynamics of subsidized fertilizer provision for lowland rice farming through the RDKK mechanism in Kendari City, to find out the percentage of subsidized fertilizer proposals for lowland rice farmer groups in Baruga and Labibia villages through RDKK that the government could fulfill in the last 2 years, to find out farmers' anticipation. Farmer groups when the subsidy fertilizer proposal submitted through RDKK cannot be fully fulfilled by the government. This research was conducted in Baruga and Labibia in August-December 2020. The research method is qualitative. The results of this study indicate that the process of providing fertilizer is in accordance with the flow of subsidized fertilizer provision according to government regulations, but in the preparation of RDKK to propose the amount of subsidized fertilizer in Labibia is still assisted by extension agents, while in Kelurahan Baruga it is carried out by the head of the farmer group. The government does not always fully fulfill subsidized fertilizers due to the limited budget and quota allocation for subsidized fertilizers. This is done by farmers in Baruga Village by purchasing non-subsidized fertilizers, or looking for farmers / farmer groups who still have leftover fertilizer rations at retailers. Meanwhile, in Labibia, the anticipation occurred because the price of subsidized fertilizers based on HET was still relatively expensive, so they preferred to use non-subsidized fertilizers which were not in accordance with government recommendations and did not fertilize at all because the rice fields were mostly classified as fertile.